China's road towards sustainable development: Geography bridges science and solution. (October 2019) - Liu, Hongyan; Leng, Shuying; He, Canfei; Peng, Jian; Piao, Shilong; Wang, Xuejun
Seventeen sustainable development goals (SDGs) were put forward at the United Nations Development Summit in 2015 when releasing "Transforming our world: The 2030 Agenda for Sustainable Development". However, the international community still lacks understanding of how to make a bridge between scientific research and SDGs. China has experienced 40 years of rapid economic growth and social development, which have imposed considerable challenges on sustainable development. Although many disciplines have made contributions to promoting sustainable development in China, how to bridge SDGs and scientific research is still not fully clear. In this paper, we review the contribution of geographers to this issue to provide references for further international efforts towards meeting the SDGs. We consider three aspects in particular: the sensitive process capture of regional responses and feedbacks to global change; the cognition and geographical solution of human–environment conflicts; and the mutual promotion of spatial governance and geographical practices. The contribution of geography as a discipline to the sustainable development of China is an epitome of geographers' efforts over the world. The practices experienced in China show that geography has played an irreplaceable role in promoting sustainable development, and can deal effectively with the challenges posed to the academic community by SDGs. As a discipline, geography has been deeply integrated into sustainable development. In the future, geography should become a key discipline in integrating many disciplines involved in sustainable development studies, and provide real-time decision support systems for sustainable development by combining big data and artificial intelligence.